Development of remote control for thermoplastics dosing automation system - Sotnik, S. V.; Trokhin, V. V.; Tereshchuk, D. О. (My University, 2024)
This paper focuses on automation aspects of plastic molding processes, namely thermoplastics dosing. The main components of automation systems are briefly considered. The key features of development are presented. The structure of injection molding machine and processes that take place in it are studied. As result, virtual console for regulating and controlling dosing process was developed using trendy Scada package. This is ergonomic console that provides operator with user-friendly interface for precise control of dosing process, ensuring high quality and production efficiency.
Keywords: automation system; control panel; thermoplastic; plastic molding processes